Adapting 'Tame Your Gut' for patients with inflammatory bowel disease and co-morbid anxiety and/or depression. (January 2022) - Hanlon, Inna; Hewitt, Catherine; Evans, Subhadra; Taylor, Jo; Selinger, Christian; Mikocka-Walus, Antonina
This qualitative study collected stakeholders' views on adapting an existing online psychotherapy programme, 'Tame Your Gut', to the needs of patients with inflammatory bowel disease (IBD) and comorbid anxiety and/or depression. Adult patients ( n = 13) and health professionals ( n = 12) participated in semi-structured focus groups or interviews, analysed with a thematic analysis. Patients had a generally positive attitude towards 'Tame Your Gut', while health professionals saw it as useful for selected patients only. Both groups indicated their preference for clinician-assisted online psychotherapy. 'Tame Your Gut' is acceptable to patients and health professionals but only when supported by clinicians.